1966
DOI: 10.3402/tellusa.v18i2-3.9200
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanism of formation of radon daughter aerosols

Abstract: The formation of radon daughter aerosols in air is found to be markedly influenced by the presence of charges and vapours. Experiments have been carried out with natural radon in the air to show that radon daughter products behave as single ions of high mobility in filtered dry air whereas they are attached to cluster aerosols formed in the presence of certain charges and vapours. In these experiments the cluster aerosols have been formed with ethanol vapour in the presence of small negative ions. Knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In atmospheric air, short-lived radon decay products behave like ions with high mobility, and easily adsorb on various types of aerosols [26,27]. In the case of gas transport by gas pipeline, similar behavior can be noted, which consequently leads to the accumulation of 210 Pb on aerosols and, finally, black powder.…”
Section: Transport Model Of 210 Pb In the Gas Pipelinementioning
confidence: 92%
“…In atmospheric air, short-lived radon decay products behave like ions with high mobility, and easily adsorb on various types of aerosols [26,27]. In the case of gas transport by gas pipeline, similar behavior can be noted, which consequently leads to the accumulation of 210 Pb on aerosols and, finally, black powder.…”
Section: Transport Model Of 210 Pb In the Gas Pipelinementioning
confidence: 92%
“…The method of determination of equilibrium daughter product activity waa baaed on an earlier study which showed that when highly filtered and dried air mixed with submicron aerosol was allowed to stay for 3 hours in a reservoir, the radon in the air decayed and attained equilibrium with its short-lived daughter products which attached to the aerosol. The details of the method have been described in an earlier paper (Vohra, Subba Ramu & Mohan Rao, 1966). The samples were filled in the reservoir for periods of 30 minutes, along with the aerosol and after the stagnation time of 3 hours, the radon daughters attached to aerosols were collected on a millipore filter paper and their activity measured using an alpha scintillation counter.…”
Section: Measurementsmentioning
confidence: 99%